C–H functionalization of cyclic amines: redox-annulations with α, β-unsaturated carbonyl compounds1. Issue 53 (7th July 2015) - Kang, YoungKu; Richers, Matthew T.; Sawicki, Conrad H.; Seidel, Daniel
<x xml:space="preserve">Abstract</x> Pyrrolidine and related amines undergo carboxylic acid promoted redox-annulations with α, β-unsaturated ketones via the intermediacy of conjugated azomethine ylides.